Autoimmune thyroiditis and diabetes mellitus type 1 after long-term gonadotropin-releasing hormone agonist treatment for central precocious puberty: evolution or coincidence? - Marina Krstevska-Konstantinova; Aleksandra Jancevska; Zoran Gucev (Walter de Gruyter GmbH, 2010)
Very few abnormalities in endocrine function have been reported during long term gonadotropin-releasing hormone agonist (GnRHa) treatment in girls. Most authors agree that this therapy is safe and effective. We present an unusual outcome of long term GnRHa therapy in two girls with central precocious puberty(CPP) of idiopathic or organic origin. They have received monthly depot injections of triptorelin acetate for a time period of 8 years. Thyroid function was examined by measuring serum levels of thyrotropin (TSH), thyroxine (T4), thyroid antibodies, and ultrasound of the thyroid gland. One of the girls was at the age of 8.5 years, having elevated thyroid antibodies, mild goitier and an abnormal ultrasound of the thyroid gland, suggesting autoimmune thyroiditis. Another girl with a hypothalamic hamartoma developed diabetes mellitus at the age of 9 years. Both of these girls were early diagnosed for CPP, at 6 months and 8 months respectively, and given GnRHa treatment. So far, it is not known whether these autoimmune diseases are related to the GnRHa treatment or are simply a coincidence. However, we suggest a closer monitoring of girls with CPP who have had a long period of treatment
Keywords: precocious puberty; GnRH treatment; hypothalamic hamartoma; autoimmune thyroiditis